Qualitative Insights Into Consumer Satisfaction Strategies at Padma Hotel Semarang: The Role of Facilities and Services - Berliana, Ina; Wijoyo, Tuwuh Adhistyo (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
This research aims to explore the strategies employed by Padma Hotel Semarang to enhance consumer satisfaction through its facilities and services, with a focus on identifying the key factors that contribute to a superior guest experience. Using a qualitative research approach, data was collected through semi-structured interviews with heads of department, including the Front Office Manager, Marketing Manager, and Food and Beverage Manager, as well as non-participant observations within the hotel’s key operational areas. The study highlights the importance of high-quality facility management, personalized service delivery, integrated marketing strategies, and effective cross-departmental collaboration in shaping guest satisfaction. The findings reveal that Padma Hotel Semarang’s commitment to maintaining excellent facilities, offering tailored services, utilizing customer feedback, and fostering collaboration across departments contributes significantly to a positive guest experience. This research provides valuable insights for hotel management professionals seeking to improve service quality and customer loyalty. The originality of this study lies in its focus on qualitative insights from department heads, offering a deeper understanding of the strategies behind consumer satisfaction in a luxury hotel setting